Analysis of SHEIN Brand's Success in Overseas Markets Online from the Perspective of Consumer Psychology: Key Factors of Social Media Marketing - Jin, Xiao; Wang, Qinxin (International Journal of Global Economics and Management, 2024)
Established in Nanjing in 2012, SHEIN has emerged as a powerhouse in the global e-commerce realm, boasting sales exceeding 100 billion yuan by 2021 and dethroning Amazon as the most downloaded shopping app. This paper examines how SHEIN, by mastering people's psychology, employs an integrated marketing strategy that combines social media, user-generated content, search engine optimization, short videos, and live streaming to get consumers interested in its clothing [4]. The analysis is made based on the Demand Theory that consumers are sensitive to price and SHEIN always adheres to the idea of buying fashionable goods at cheap prices.  The study distills valuable insights for Chinese brands eyeing cross-border e-commerce, advocating for a strategic emulation of SHEIN's consumer-centric approach to thrive in the international marketplace.